PEMBERDAYAAN MASYARAKAT MELALUI PEMBUATAN SELAI JERUK DI JORONG KAMPUNG MUARO NAGARI KOTO TINGGI KECAMATAN GUNUNG OMEH KABUPATEN LIMAPULUH KOTA - Weriantoni Weriantoni; Nadailla Mahsyuri (Buletin Ilmiah Nagari Membangun, 2019)
Nagari Koto Tinggi which located in Gunuang Omeh Subdistrict in Regency 50 Kota is one of the biggest producers natural products of orange in West Sumatra. Jeruk Siam Gunuang Omeh (JESIGO), has good quality, but post-harvest processing is still lacking. The Orange produced at Nagari Koto Tinggi has a delicious, sweet and evenly large size. One of the results from the utilization of orange is jam. Processed from orange that is easy to make is jam. The Utilization of orange in Nagari Koto Tinggi to jam is expected to be an added value for the community in Nagari Koto Tinggi. Andalas University students in conducting KKN (Real Work Lecture) activities help run one of the work programs to the community that is socialization of making orange jam. The socialization went well by involving women's PKK of Jorong Muaro. The resulting orange jam is quite satisfying, because orange jam has an aftertaste that is less desirable, but the results are still acceptable. This orange jam formulation is still in an experimental phase, so further research is needed to determine the composition in making delicious jam. Until then this jam is expected to be one of the selling points for Koto Tinggi village.